AN ANALYSIS OF CODE-MIXING IN DEDDY CORBUZIER’S YOUTUBE VIDEOS - Dhinna Liezantica A’nnur (ReALL - Research on Applied Linguistics and Literature, 2022)
This research is an analysis about the code-mixing phenomenon which happens in videos. The purposes of the research are (1) to find out the types of code-mixing used in YouTube video by Deddy Corbuzier; (2) to describe Deddy Corbuzier’s factors for using code-mixing in his YouTube video. In this research, descriptive qualitative research was used to reveal the social phenomenon in relation to code-mixing issues. The grand theory of this research is sociolinguistics about code-mixing based on Hoffman’s theory which describes the types of code-mixing and Holmes’s theory which describes the factors of code-mixing. The object of this research was the utterances from Deddy Corbuzier’s YouTube video. There are four videos which are selected based on motivation categories. From the data analysis, it shows that Deddy Corbuzier used outer code-mixing as he mixed his Indonesian utterance with an element derived from English. In his utterances, he often used intra-sentential mixing in the form of word. Based on the data analysis, the researcher has found five factors which support Deddy Corbuzier to use code-mixing in his utterances. There are (1) bilingualism and multilingualism; (2) discussed a particular topic; (3) social dimension; (4) formality dimension; (5) goal of the interaction. The dominant factors which support this code-mixing are bilingualism and goal of the interaction.